Praychological Experiences of Sifon for Women in Timor Island - Maria Syelvrida Tumina; Sri Yona; Agung Waluyo; Eusabius Separera Niron (GLOBAL HEALTH SCIENCE GROUP, 2024)
Sifon is a post-circumcision ritual of sexual intercourse in the Atoin Meto tribe with women who are not their partners. Sifon women have various reasons for doing this practice such as fulfilling their economic and daily needs. Most of Sifon women are the heads of families. In addition to having an impact on the risk of contracting HIV, AIDS and STD Infection, Sifon also has other impacts on women such as social stigma and shameful accusation. Objective:The purpose of this study is to explore the psychological experiences of Sifon women in Timor Island.Method:This study used a phenomenological approach and purposive sampling technique. Participants were with inclusion criteria. They have to be more than 18 years old and have practiced Sifon in the last 6 (six) months. Data collection was carried out from March to July 2020 in Kupang Regency and South Central Timor Regency, East Nusa Tenggara Province. The data was processed using Collaizi method.Results: There were 13 women who were successfully interviewed and 7 of them shared their psychological experiences. Most of them are farmers, have elementary school education and become the head of their families. Based on the results of data analysis, the researcher found 3 themes: (1) feeling shameful, (2) feeling humiliated and not worthed, (3) having trauma.Conclusions:The decision to become a Sifon woman was made with various considerations, including meeting economic needs and earming money for all family members. It is necessary to take a culturally sensitive approach and deeper psychological assistance with Sifon women to help improve their wellbeing. The findings of this study show that most of these Sifon women are heads of families.